Improving Employees Retention to Ensure Sustainability - Ramli, Nur Afifah Mohd (2014)
Attrition is defined as a gradual reduction in the number of workforce through retirement, resignation or death. In other words, it can also be said as employee turnover. This management project was based on rising attrition issue faced by a new company in Penang semiconductor outsourcing industry, called STU Global. Even though just operated in Malaysia in less than three years, rising attrition is considered challenging and need to be solved. The impact of rising attrition has received considerable attention by management and human resource professionals. It has been proven to cost more the organization and impacting the business and long term plan of the organization.